Antibodies to Lactobacilli and Bifidobacteria in Young Children with Different Propensity to Develop Islet Autoimmunity. (4th March 2014) - Talja, Ija; Kubo, Anna-Liisa; Veijola, Riitta; Knip, Mikael; Simell, Olli; Ilonen, Jorma; Vähä-Mäkilä, Mari; Sepp, Epp; Mikelsaar, Marika; Utt, Meeme; Uibo, Raivo
Abstract : The intestinal microbiota is essential to the maturation and homeostasis of the immune system. Immunoblot assays were used to establish the prevalence of serum IgG, IgM, and IgA antibodies specific for Bifidobacterium adolescentis, Bifidobacterium longum, and Lactobacillus rhamnosus GG proteins in young children presenting with or without type 1 diabetes (T1D). We demonstrated that children between the ages of 6 and 12 months had a substantial increase in the frequency of IgG antibodies specific for L. rhamnosus GG proteins. We measured IgG, IgM, and IgA class antibody reactivity against B. adolescentis DSM 20083, B. adolescentis DSM 20086, and B. longum DSM 20088 proteins demonstrating significantly higher IgA responses against B. adolescentis DSM 20083 strain proteins in children who developed islet autoimmunity and T1D later in life. B. adolescentis strains showed more IgM type antibodies in children who developed T1D later in life, but the difference was not statistically significant. B. longum proteins were recognized by IgG and IgA antibodies to a higher extent compared to other bacteria studied. These results confirm that differences in immune reactivity against some commensal strains in young children may represent a different risk factor for developing T1D.